Improving the Students’ Vocabulary Mastery by Using Word Cloud at The Tenth Grade of SMK Negeri 1 Gunungsitoli In 2022/2023 - Arlina Laoli; Yasminar Amaerita Telaumbanua; Adieli Laoli; Afore Tahir Harefa (English Education Department at FKIP Nommensen University, 2023)
Vocabulary mastery is a skill that refers to a high level of proficiency in processing words in a language. The students at the tenth grade of SMK Negeri 1 Gunungsitoli lacked vocabulary mastery, so they found it difficulty to understand texts properly and did not achieve the minimum competency criteria (MMC) that has been set at school. The purpose of this study was to improve the students' ability to vocabulary mastery. In improving students' vocabulary mastery, the researcher used Word Cloud and applied it in Classroom Action Research (CAR). This research was conducted in Cycle II, there were four steps in conducting research, namely: planning, action, observation and reflection. . In Cycle I, there was no student who was classified in